Greening the Workforce: The Strategic Role of Green HRM in Building Engagement and Environmental Responsibility in Tourism - Sinaga, Endang Komesty; Sihombing, Irene Hanna H. (Journal of Tourism, Hospitality and Travel Management, 2024)
This study investigates the role of Green Human Resource Management (GHRM) practices in enhancing employee engagement and environmental performance within the Indonesian tourism industry. Drawing upon the Resource-Based View (RBV), this research conceptualizes green recruitment, training, performance appraisal, and compensation as strategic organizational resources that cultivate pro-environmental behavior among employees. Using a quantitative approach and Structural Equation Modeling–Partial Least Squares (SEM-PLS), data were collected from 287 employees in various tourism sectors, including hotels, travel agencies, and eco-tourism operators. The results reveal that all GHRM dimensions significantly influence employee engagement and environmental performance, with green training and green compensation showing the strongest effects on engagement. Additionally, the findings highlight the mediating role of employee engagement, indicating that employees' psychological attachment to sustainability values is a critical pathway for translating GHRM practices into improved environmental outcomes. Theoretically, This study contributes by reaffirming the RBV perspective that human capital becomes a source of competitive advantage when aligned with environmental values. Philosophically, the research illustrates a shift toward value-based HRM, positioning employees as ecological stewards. The findings offer actionable insights for practitioners, emphasizing the need for tourism organizations to integrate environmental values into H.R. systems to foster a proactive green workforce. Future research is recommended to explore the long-term impacts of GHRM and the role of leadership in deepening the green psychological contract within organizations.